Good-bye, middle school - Suzanne, Jamie; Pascal, Francine; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1998)
Sweet Valley Middle School is over-crowded and twins Jessica and Elizabeth may be moved to a new junior high. The twins and their friends plan to spend what might be a final night together, camping out and playing Truth or Dare. But these friends who thought they knew one another so well are about to discover a truth more shocking than any dare.
Keywords: Twins -- Fiction; Friendship -- Fiction; Young adult fiction